Ways of Developing Small Business and Private Entrepreneurship in the Republic of Uzbekistan (Eurasian Research Bulletin, 2022)
This article describes ways to develop small business and private entrepreneurship in the Republic of Uzbekistan. The article notes the development of small business and private entrepreneurship. Questions are discussed for improving the business environment. The author presents approaches to the measures to further improve the business environment for the development of small business and private entrepreneurship and their free activity. The existing problems in this sector are analyzed. And also, some recommendations for their solution have been worked out.